Biofilm production and its correlation with antibiogram among clinical isolates of uropathogenic Escherichia coli - Yadav, Monika; Khumanthem, Sulochana D.; Kshetrimayum, Mamta D.; Damrolien, Shan (International Journal of Advances in Medicine, 2018)
Background: Urinary tract infection (UTI) is one of the commonest health problem encountered in clinical practice. The biofilms play major role in decreasing the susceptibility to the antimicrobial agents. The present study aimed at isolation and identification of Escherichia coli from cases of urinary tract infection, and to find out production of biofilms by these isolates and to correlate it with antimicrobial resistance. Methods: This study was a cross sectional study. Urine specimen from patients suspected of UTIs were collected and processed by standard operative procedure, antibiotic susceptibility test was done by Kirby Bauer disc diffusion method. Biofilm production in isolates was done by Tissue culture plate (TCP) method, Christensen’s test tube (CTT) method, and Congo red agar (CRA) method. Results: Out of the total of 250 isolates 191 (76%) showed biofilm positive by TCP method, 180 (72%) showed biofilm positive by CTT method, 161 (64%) showed biofilm positive by CRA method. 90% of total extended spectrum beta lactamase (ESBL) producing Escherichia coli were biofilm producers. There is more resistance for each and every antibiotic among biofilm producers in comparision to biofilm non producers. Conclusions: The microbial biofilms may pose a public health problem, as the microorganisms in the biofilms are difficult to be treated with antimicrobial agents.